Stroboscopic vision and sustained attention during coincidence-anticipation. Issue 1 (December 2017) - Ballester, Rafael; Huertas, Florentino; Uji, Makoto; Bennett, Simon
Abstract We compared coincidence-anticipation performance in normal vision and stroboscopic vision as a function of time-on-task. Participants estimated the arrival time of a real object that moved with constant acceleration (−0.7, 0, +0.7 m/s2 ) in a pseudo-randomised order across 4 blocks of 30 trials in both vision conditions, received in a counter-balanced order. Participants (n = 20) became more errorful (accuracy and variability) in the normal vision condition as a function of time-on-task, whereas performance was maintained in the stroboscopic vision condition. We interpret these data as showing that participants failed to maintain coincidence-anticipation performance in the normal vision condition due to monotony and attentional underload. In contrast, the stroboscopic vision condition placed a greater demand on visual-spatial memory for motion extrapolation, and thus participants did not experience the typical vigilance decrement in performance. While short-term adaptation effects from practicing in stroboscopic vision are promising, future work needs to consider for how long participants can maintain effortful processing, and whether there are negative carry-over effects from cognitive fatigue when transferring to normal vision.